Using of turquoise organization’s concept to benchmark indicators of creative team management - A. R. Akopyan; Yu. V. Vorontsova (Вестник университета)
The purpose of this study is to study the possibilities of applying the turquoise type organization model in creative industries, where there is a need for constant staff development to achieve maximum results. When analyzing the turquoise organization model, a number of factors should be taken into account, on which it relies, and also choose from a number of them those that really have a significant impact on the formation of the turquoise approach in creative industries. At a certain stage, from a non-standard creative management model, one way or another, it is necessary to return to traditional management methods while maintaining the basic principles of the turquoise organization, which can be considered as a standard. The introduction of such tools into the creative team/process management system qualitatively improves the mechanism of managerial decision-making, and also allows it to be debugged through unidirectional actions of both managers and the entire creative team. To implement the task of standardization, a universal model of quantitative assessment of qualitative indicators was developed, taking into account the dynamics of their changes. At the same time, a model was built for selecting indicators for the formation of a set of personnel characteristics in order to benchmark them relative to the level of the same characteristics of the turquoise organization, taking into account the possibility of their transversal change over time.